Evaluation of the Ph‐3 gene‐specific marker developed for marker‐assisted selection of late blight‐resistant tomato. (5th August 2016) - Wang, Ya‐Ying; Chen, Chien‐Hua; Hoffmann, Annika; Hsu, Yun‐Che; Lu, Shu‐Fen; Wang, Jaw‐Fen; Hanson, Peter
Abstract: Late blight caused by Phytophthora infestans is one of the most destructive diseases of tomato ( Solanum lycopersicum L.) that mainly occurs in cool and wet environments. With the spread of the A2 mating type and new clonal lineages, fewer fungicides provide effective control of the disease, which has increased its worldwide threat. Host resistance could contribute significantly to sustainable disease control. Ph‐3 is a race‐specific late blight resistance gene commonly used in commercial tomato breeding. Availability of precise and easy to use gene‐based markers would facilitate selection. In this study, a Ph‐3 on‐gene cleaved amplified polymorphic sequence (CAPS) marker, Ph3.gsm/ Hin cII, was developed based on the published gene sequence of Ph‐3 . The effectiveness of the marker was evaluated along with other published Ph‐3 markers using an F9 recombinant inbred line (RIL) population derived from NC 23E‐2(93) × L3708. Markers Ph3.gsm/ Hin cII and TG328/ Bst NI accurately genotyped the RIL population for Ph‐3 . In addition, Ph3.gsm/ Hin cII was able to differentiate variable susceptible alleles. This reliable codominant DNA marker would be very useful in marker‐assisted selection, particularly for resistance gene pyramiding.